2021
DOI: 10.1038/s41419-021-04428-7
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA GSEC promotes neutrophil inflammatory activation by supporting PFKFB3-involved glycolytic metabolism in sepsis

Abstract: Metabolic reprogramming is a hallmark of neutrophil activation in sepsis. LncRNAs play important roles in manipulating cell metabolism; however, their specific involvement in neutrophil activation in sepsis remains unclear. Here we found that 11 lncRNAs and 105 mRNAs were differentially expressed in three transcriptome datasets (GSE13904, GSE28750, and GSE64457) of gene expression in blood leukocytes and neutrophils of septic patients and healthy volunteers. After Gene Ontology biological process analysis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…Measurement of neutrophil apoptosis after 24h incubation showed that increasing concentrations of 3PO increased the number of late apoptotic cells and decreased the early apoptotic cell count, without significantly altering the overall proportions of live/apoptotic cells. Enhancement of PFKFB3 transcription and translation facilitates the production of neutrophil inflammatory factors has been identified during the acute phase of sepsis [42]. Pharmacological inhibition or depletion of PFK-2 by small interfering RNA (siRNA) leads to a significant decrease in NOX2 activity response to various neutrophil stimuli [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurement of neutrophil apoptosis after 24h incubation showed that increasing concentrations of 3PO increased the number of late apoptotic cells and decreased the early apoptotic cell count, without significantly altering the overall proportions of live/apoptotic cells. Enhancement of PFKFB3 transcription and translation facilitates the production of neutrophil inflammatory factors has been identified during the acute phase of sepsis [42]. Pharmacological inhibition or depletion of PFK-2 by small interfering RNA (siRNA) leads to a significant decrease in NOX2 activity response to various neutrophil stimuli [43].…”
Section: Discussionmentioning
confidence: 99%
“…It has the highest kinase:phosphatase activity ratio of all the PFKFB isoforms [44], proving a possible explanation as to why inhibition of this isoform has such a marked effect on cellular function. In vitro experiments showed glycolytic metabolism with PFKFB3 involvement supports inflammatory cytokine expression [42]. Furthermore, a significant increase has been observed in the expression of PFKFB3 in LPS-challenged and sepsis neutrophils compared to controls [45].…”
Section: Discussionmentioning
confidence: 99%
“…After washing with a washing buffer to remove unbound substances and antibodies, a stop solution was added to terminate the color development, and the OD value at 540 nm was measured in an ELISA plate reader. The concentrations were calculated from the standard curve and multiplied by the dilution factor to obtain the results 21 …”
Section: Methodsmentioning
confidence: 99%
“…Further studies on the effect of Leishmania infection on neutrophil metabolic programme are required to determine the implications of metabolic shifts on neutrophil effector response and parasite survival. Regulation of glycolytic metabolism mediated by long non‐coding RNAs (lncRNAs) regulates mRNA levels of 6‐phosphofructo‐2‐kinase/fructose‐2,6‐biphosphatase 3 (PFKFB3) in human leukaemia 60 cell line, (HL‐60), which affects inflammatory cytokines expression 68 . The presence of lncRNA in the blood transcriptome of VL patients infected with Leishmania infantum opens a new gate for research on the potential implications of this novel class of gene regulators in the regulation of neutrophil transcriptional programme and other immune cells transcriptionally active during infection such as T cell and NK cells 69 …”
Section: Impact Of Transcriptional Plasticity On Neutrophils Effector...mentioning
confidence: 99%